Comparative study for evaluation of eggs age by means of floating in water - ΓΙΩΤΗΣ Α.; ΧΑΡΙΣΗΣ Φ.; ΠΑΠΑΝΑΣΤΑΣΙΟΥ Κ.; ΜΑΖΑΡΑΚΗΣ Θ.; ΝΑΘΑΝΑΗΛ Θ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The results of floating the eggs, for estimation of their age, preserved in diferent temperature levels were studied. 120, six hours old eggs, were devided in 4 groups. Three groups were put respectively in 32C, 21°-22°C, 0°-l°C for 41 days. The fourth group was put in 0°-l°C. after embedding the eggs instantaneously in liquid paraffin. The eggs were daily controled for floating in water. The results were shown that preservation temperature influences the floating ability of eggs. Eggs preserved in low temperatures appear younger then their real age.